Covid‐19 pandemic and pregnancy - Hayakawa, Satoshi (J Obstet Gynaecol Res, 2020)
At the end of 2019, a new coronavirus disease, COVID‐19, emerged and quickly spread around the world. Severe acute respiratory syndrome Coronavirus 2 (SARS‐CoV‐2), the causative virus of this disease, belongs to the β‐coronavirus family, together with SARS and middle east respiratory syndrome, and has similar biological characteristics to these viruses. For obstetricians, the susceptibility and prognoses of pregnant women and the effects of the infection on the fetus have been the focus of attention; however, at present, the seriousness of the disease in pregnant women is not apparent, and COVID‐19 does not increase the rate of miscarriage, stillbirth, preterm labor or teratogenicity. Even so, carriers might transmit SARS‐CoV‐2 to pregnant women. Thus, we must keep in mind that all medical personnel must understand and maintain standard precautions in their clinical and laboratory practices.